1994
DOI: 10.3164/jcbn.16.27
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Activated Polymorphonuclear Leukocytes in Galactosamine-Induced Hepatic Injury in Rats.

Abstract: This study attempted to elucidate the pathological role of peripheral blood polymorphonuclear leukocytes (PMNs) in the damage to hepatic sinusoidal endothelial cells (HSECs) in hepatic injury. Wistar male rats weighing about 200 g received a single injection of 1 g/kg body weight of galactosamine (GalN) intraperitoneally for the induction of hepatitis. The level of serum glutamic pyruvate transaminase activity increased time-dependently concomitantly with serum endotoxin level and hepatic lipid peroxide conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, the hepatic activities of antioxidant enzymes such as SOD, catalase, and GSH-px are known to decrease in rats treated with GAL (Korda, 1996). Several reports have shown an increase in hepatic lipid peroxidation with liver injury development in GAL-treated rats (Seçkin et al, 1995;Hino et al, 1994;Sun et al, 2003), although Mourelle and Meza (1989) have reported that hepatic lipid peroxide level begins to increase before the onset of liver injury in GAL-treated rats. In the present study, treatment of rats with GAL (500 mg/kg body weight) caused an increase in the hepatic concentration of TBARS, an index of lipid peroxidation, at 24 h, but not at 6 h, after hepatotoxin treatment, as shown in our previous report (Ohta et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the hepatic activities of antioxidant enzymes such as SOD, catalase, and GSH-px are known to decrease in rats treated with GAL (Korda, 1996). Several reports have shown an increase in hepatic lipid peroxidation with liver injury development in GAL-treated rats (Seçkin et al, 1995;Hino et al, 1994;Sun et al, 2003), although Mourelle and Meza (1989) have reported that hepatic lipid peroxide level begins to increase before the onset of liver injury in GAL-treated rats. In the present study, treatment of rats with GAL (500 mg/kg body weight) caused an increase in the hepatic concentration of TBARS, an index of lipid peroxidation, at 24 h, but not at 6 h, after hepatotoxin treatment, as shown in our previous report (Ohta et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…These results also suggest that this preventive effect of TJ-15 on the disruption of hepatic antioxidant defense systems in GAL-treated rats may be involved in its preventive effect on the progression of GAL-induced liver injury. Hino et al (1994) reported that, in rats treated with GAL, neutrophil infiltration into the liver cells increased with the formation and progression of liver injury and that ROS, such as O 2 − , released from activated neutrophils infiltrating into the liver of GAL-treated rats caused the extension of liver cell necrosis. We have shown in rats treated with GAL (500 mg/kg body weight) that neutrophil infiltration into the liver cells occurs at an early stage of liver injury and is enhanced at a progressed stage of the injury (Ohta et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation